Metathetic Sulfur Transfer mediated by N-(2-aminophenyl)-4-methyl-thiazolin-2-thione derivatives: Part III: a new Route to Diversely Substituted S-alkyl thioesters. - Mehdid, Mohammed Amine; Djafri, Ayada; Andreoli, Federico; Vanthuyne, Nicolas; Farran, Daniel; Niebler, Johannes; Büttner, Andrea; Giorgi, Michel; Roussel, Christian (Tetrahedron, 2013)
A metal free synthesis of S-alkyl thioesters, which does not involve alkylthiol or thiocarboxylic acid as sulfur source is disclosed. The process involves first an acylation at the nitrogen of the readily available N-(2-aminophenyl)-4-methyl-thiazolin-2-thione, second an alkylation at sulfur of the resulting amides and finally a base catalyzed metathetic reaction, which provides under very mild conditions and in high isolated yields the S-alkyl thioesters. An ion-pair intermediate (9-acyl-3-methyl[1,3]thiazolo[3,2-a][3,1]benzimidazol-9-ium alkylthiolate) accounts for the formation of mixed thioesters during cross-coupling experiments. S-Alkyl diversity is provided by the alkylating agent and the acyl diversity comes from the acylating agent, while the sulfur atom is provided by the heterocycl